Socio-economic impacts of different categories of state expenditure in urban and rural regions - Makkonen, Teemu; Lehtonen, Olli; Inkinen, Tommi; Vihinen, Hilkka; Vuotilainen, Olli (Routledge, 2025)
Decisions regarding the geographical allocation of state expenditure are important factors determining regional development and cohesion. However, the topic has received little scholarly attention due to limited data availability. Here such data were collected to uncover how state expenditure is allocated in Finland. The results reveal that while the Finnish state expenditure system is a redistributive one, the current structure of state expenditure does not stir convergence between the already socio-economically well-off and less advanced regions. This is because most of the funding received by the less developed municipalities are sustaining the current regional structure rather than regenerating economic development.